2012
DOI: 10.7126/cdj.2012.1446
|View full text |Cite
|
Sign up to set email alerts
|

Handedness of orthodontists and its impact on practice

Abstract: <p><strong>Objective:</strong> To assess the handedness prevelance of orthodontists and analyse the discomfort of left-handed orthodontists on practice.</p><p><strong>Materials and Methods:</strong> A questionnaire about the laterality of orthodontists and their discomfort was prepared and distributed to our orthodontic society members. 173 questionnaires were investigated.</p><p><strong>Results:</strong> Fifteen of the participants were left-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Similar results were found in studies done by Odabas et al, 13 Kapoor et al, 12 Silva et al, 2 and Silva et al, 14 but contrasting result was found in the study done by Al-Johany, 8 in which 63% were males and 47% were females. Maximum number of participants (57.3%) was from age group 23 to 26 years.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were found in studies done by Odabas et al, 13 Kapoor et al, 12 Silva et al, 2 and Silva et al, 14 but contrasting result was found in the study done by Al-Johany, 8 in which 63% were males and 47% were females. Maximum number of participants (57.3%) was from age group 23 to 26 years.…”
Section: Discussionsupporting
confidence: 82%
“…Still regarding inclusion in the educational environment, the majority of left-handed participants in a study [29] reported that they preferred an educational model that took into consideration the lateral dominance of students and it would be more functional if at least the equipment was mobile/reversible. Some students described reduced clinical performance due to back pain and inadequate work posture.…”
Section: Discussionmentioning
confidence: 99%
“…It is pertinent to mention that both this and the Nigerian studies used the Edinburgh Handedness Inventory questionnaire (Alibeik and Angaji, 2010). The global prevalence of left-handedness has not yet been established (Odabas et al, 2012). However, it was estimated that 10% of the world's population are left handers (Lui et al, 2012).…”
Section: Theme 4: Consequencesmentioning
confidence: 99%